Clinical ethics consultation among Italian ethics committee: A mixed method study. - Ludovica De Panfilis; Domenico Franco Merlo; Roberto Satolli; Marta Perin; Luca Ghirotto; Massimo Costantini (PLoS ONE)
Objective The general purpose for ethics consultations is to deliberate on issues on medical and scientific research and act towards the safeguard of the patient's rights and dignity. With the implementation of European Union (EU) Regulation 536/2014 on clinical trials and cost and time-optimization, the nature of consultations and the bodies they are carried out might be to some extent affected. Accordingly, we sought to gain an updated perspective on the current role and current practices of ethics consultations nationwide in both clinical and research settings. Methods The study was carried forth by a three-step mixed-method approach: i) review of policies/regulations for ethics committee (EC) nationwide; ii) a structured survey on ethics consultation activity completed by each EC during 2016; iii) incorporated into the third part, a qualitative assessment with a selected sample of 8 key-informants for a semi-structured interview, discussing EC history, the ethics consultation function, and the professional experience of consultants. Results Review of the policies/regulations promoted by ECs showed that 72,6% (n = 69) of all the ECs (N = 95) being actually capable of providing ethics consultation service by policy. 71 ECs (74.7%) responded to the survey on ethics consultation requests; among them, 48 (67.6%) provided ethics consultations of which 23 (23/48) actually received requests for this service in the year 2016. Many ECs did not have a structured database in place to provide precise figures of requests received in the last year nor of their contents. Conclusion To date, ethics consultation in clinical and research practice is largely underappreciated and not well understood by users. The consultants themselves lack a comprehensive vision of work carried out in their field, and bioethics training programs to keep them updated. Despite clinical ethics consultation services should not necessarily be mandatory, following the recent EU Regulation on clinical trials, institutional ethics consultation bodies should be re-evaluated.